(Re)examining the effects of athlete brand image (ABI) on psychological commitment: an empirical investigation using structural equation modelling (SEM) and fuzzy set qualitative comparative analysis (fsQCA). Issue 2 (15th March 2019) - Väätäinen, Merituuli; Dickenson, Peter
ABSTRACT: Research question: How does athlete brand image (ABI) affect psychological commitment (PC) when operationalised at the dimension- (attribute-) level, and measured using reflective indicators? Previous studies operationalise ABI at a higher-order construct level, and/or measure ABI using formative measures. Such operationalisations obscure potentially different relationships between ABI's image attributes and PC. Research methods: A questionnaire was used to collect data from 197 UK respondents over a six-day period within two weeks of the Rio 2016 Olympics concluding. Data were analysed through structural equation modelling (SEM) and fuzzy set Qualitative Comparative Analysis (fsQCA) techniques. Results and findings: Through SEM, the ABI attributes, athletic expertise, life story, role model, and competition style are positively related to PC, sportsmanship and symbol are negatively related, and rivalry, physical attractiveness, body fit, and relationship effort are nonsignificantly related. Many structural paths between ABI's attributes and PC are also significantly different. Through fsQCA, high PC exists under three complex ABI attribute configurations, while it is absent under four complex configurations. Implications: Theoretically, finding different relationships between ABI's attributes and PC highlights why operationalising ABI at the dimension-level provides a more in-depth understanding of athlete brand image's effects on PC. Managerially, the findings suggest athletes need only a subset of ABI attributes for high PC. Subsequently, managers can more-efficiently and effectively direct resources towards those attributes that best-capitalise on athletes' images.